2019
DOI: 10.3390/molecules24234218
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiology and Behavioral Assessment of the New Molecule SMe1EC2M3 as a Representative of the Future Class of Triple Reuptake Inhibitors

Abstract: SMe1EC2M3 is a pyridoindole derivative related to the neuroleptic drug carbidine. Based on the structural similarities of SMe1EC2M3 and known serotonin (5-HT), norepinephrine, and dopamine reuptake inhibitors, we hypothesized that this compound may also have triple reuptake inhibition efficacy and an antidepressant-like effect. PreADMET and Dragon software was used for in silico prediction of pharmacokinetics and pharmacodynamics of SMe1EC2M3. Forced swim test was used to evaluate its antidepressant-like effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 46 publications
4
18
0
Order By: Relevance
“…It has indeed been reported that various CNS drugs, such typical [12] and atypical antipsychotics [12-14], tricyclic antidepressants [13], and selective 5-HT reuptake inhibitors (SSRIs) [13,15,16], increased c-Fos immunoreactivity in the amygdala, indicating an increased neural excitability in this brain area. In our previous studies, we have found that pyridoindole derivate SMe1EC2M3, a molecule with putative 5-HT reuptake inhibition properties and antidepressant-like behavioral effect [7], stimulated amygdaloid c-Fos immunoreactivity, as well [11]. The fact that SSRIinduced amygdaloid c-Fos immunoreactivity was potentiated by an antagonist of 5-HT1A autoreceptors indicated that 5-HT system is involved in the modulation of amygdaloid neural excitability by antidepressant drugs.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…It has indeed been reported that various CNS drugs, such typical [12] and atypical antipsychotics [12-14], tricyclic antidepressants [13], and selective 5-HT reuptake inhibitors (SSRIs) [13,15,16], increased c-Fos immunoreactivity in the amygdala, indicating an increased neural excitability in this brain area. In our previous studies, we have found that pyridoindole derivate SMe1EC2M3, a molecule with putative 5-HT reuptake inhibition properties and antidepressant-like behavioral effect [7], stimulated amygdaloid c-Fos immunoreactivity, as well [11]. The fact that SSRIinduced amygdaloid c-Fos immunoreactivity was potentiated by an antagonist of 5-HT1A autoreceptors indicated that 5-HT system is involved in the modulation of amygdaloid neural excitability by antidepressant drugs.…”
Section: Discussionmentioning
confidence: 96%
“…In vivo electrophysiological assessment of the excitability of 5-HT neurons of the DRN was performed as previously described [7,[42][43][44]. Adult male Wistar rats, weighing 300-350 g, were ordered from the Animal Breeding Facility of The Institute of Experimental Pharmacology and Toxicology, Center of Experimental Medicine, Slovak Academy of Sciences in DobráVoda, Slovakia.…”
Section: In Vivo Electrophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…13 , 97 , 98 Aforementioned reflections shall be considered, if study designs on the efficacy of SMe1EC2M3, a novel MRT-I with dopamine reuptake inhibiting properties, are planned in PD patients. 99 A future approval of SMe1EC2M3 is very likely, when this drug demonstrates symptomatic, motor symptoms enhancing effects in PD as initial step of the clinical development. Then as a second step, one may consider to perform long-term trials with a combination of DRT-I plus MAO-B inhibitor plus dopamine oxidation inhibitors, such as potent iron chelators, as promising future therapeutic concept to slow down progression of PD.…”
Section: Discussionmentioning
confidence: 99%
“…As in our previous study [9], we used a combination of in silico and in vivo experimental techniques to test the hypothesis that the anti-inflammatory, neuroprotective, and antidepressantlike effect of L-17 is mediated, at least in part, via the targeting of the 5-HT system. The 3-D model of L-17 was constructed, and its interaction with different 5-HT targets, such as serotonin transporter (SERT) and 5-HT receptors 3 and 1A (5-HT3/5-HT1A) was examined, used in silico calculation of the minimum binding energy.…”
Section: Introductionmentioning
confidence: 99%